Molecular characterization of lower vaginal swabs for Human papilloma virus in association with Chlamydia trachomatis infection in Cameroonian Women - Pythagore Fogue; Geraldo Djeudong; George Bouting; Elom Aglago; Gustave Simo; Smiths Lueong (Elsevier, 2018)
Human papilloma virus (HPV) infection is an etiological factor for cervical cancer development and Chlamydia trachomatis (Ct) is considered as a cofactor. Understanding the dynamics of HPV and Ct infection could help to explain the incidence of early onset of cervical cancer (CC) observed in Cameroon.Lower vaginal swabs and sera from sexually active women were analyzed for HPV and Ct infection in association with risk factors. Questionnaires were used to document patients' lifestyle and risk factors.A total of 206 women participated in the study average 28.1 ± 8 years (16-50 years). HPV prevalence was 23.3% with subtypes 16 and 18 at respectively 2.9% and 1%. Ct infection totalised 40.8%, of which 23.8% were HPV- Ct co-infections. HPV infection was inversely associated with age (p = 0.028). We found a positive association between Ct infection and the number of sex partners (p = 0.012) and a negative association with parity (p = 0.032). There was no significant association between HPV and Ct infections.High rates of HPV and Ct infections could be an indicator of cervical cancer risk in the near future. There is therefore an urgent need for sensitization as well as implementation of appropriate preventive measures. Keywords: HPV, Chlamydia trachomatis, Risk factor, Co-infection, Cervical cancer, Cameroon